Reproductive biology of Vatica venulosa Blume (Dipterocarpaceae) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Widjaya AH, Latifah D, Hardwick KA, Suhartanto MR, Palupi ER. 2021. Reproductive biology of Vatica venulosa Blume (Dipterocarpaceae). Biodiversitas 22: 4327-4337. Vatica venulosa Blume is categorized as Critically Endangered A1c ver 2.3, according to the IUCN Red List. A study of the reproductive biology of V. venulosa Blume was carried out in August 2019-February 2020 at the Research Center for Plant Conservation and Botanic Gardens, Bogor, Indonesia. The research observed flower morphology, flower development, type of pollination, fruit and seed structures. V. venulosa is categorized as having a sub-annual flowering pattern. The flowering phenology of V. venulosa from flower bud emergence until fruit senescence takes about 6 months. The flower is hermaphroditic, with position of the pistil is higher/longer than the stamen; and pollen was released prior to stigma being receptive (protandrous). V. venulosa is a cross-pollinated plant, the flower visitors are insect nymphs of Thrips sp. (Thysanoptera: Thripidae), which are white and 1-1.5 mm in size. The percentage of blooming flowers was 32.3-37.9%, fruit set 10.9 %-12.6%. Seed physiological maturity  is reached at the age of 101±3-106±3 days after the flowers bloom when the wings are yellow green or green orange in color. V. venulosa seed is a non endospermous seed, and the cotyledons are composed mainly of small clumps of starch, being 42.5% carbohydrate.
Keywords: critically endangered, flower visitors, fruit set, self-incompatible, physiological maturation, protandrous